The Effect on Performance Time and Quality of the Knots after Mono or Bimanual Training of Laparoscopic Intracorporeal Knot Tying according to the Gladiator Rule Technique - Asencio, Fernanda de Almeida; Ribeiro, Helizabet Abdala Salomão Ayroza; Romeo, Armando; Wattiez, Arnauld; Ribeiro, Paulo Augusto Galvão Ayroza (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Objective To assess whether the monomanual or bimanual training of laparoscopic suture following the same technique may interfere with the knots' performance time and/or quality.Methods A prospective observational study involving 41 resident students of gynecology/obstetrics and general surgery who attended a laparoscopic suture training for 2 days. The participants were divided into two groups. Group A performed the training using exclusively their dominant hand, and group B performed the training using both hands to tie the intracorporeal knot. All participants followed the same technique, called Romeo Gladiator Rule. At the end of the course, the participants were asked to perform three exercises to assess the time it took them to tie the knots, as well as the quality of the knots.Results A comparative analysis of the groups showed that there was no statistically significant difference (p = 0.334) between them regarding the length of time to tie one knot. However, when the time to tie 10 consecutive knots was compared, group A was faster than group B (p = 0.020). A comparison of the knot loosening average, in millimeters, revealed that the knots made by group B loosened less than those made by group A, but there was no statistically significant difference regarding the number of knots that became untied.Conclusion This study demonstrated that the knots from group B showed better quality than those from group A, with lower loosening measures and more strength necessary to untie the knots. The study also demonstrated that group A was faster than B when the time to tie ten consecutive knots was compared.
Keywords: laparoscopic training; suture training